Komposisi Kimia Tepung Jagung Varietas Unggul Lokal dan Potensinya untuk Pembuatan Mi Jagung menggunakan Ekstruder Pencetak - Muhandri, Tjahja; Zulkhaiar, Hamigia; Subarna, Subarna; Nurtama, Budi (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2019)
The objective of this researchis to identify the characteristic of Srikandi Kuning, Bisma, Sukmaraga, Lamuru and Arjuna varieties, and their potentions to be made as wet corn noodle.  Corn noodles were processed using forming extruder model MS9, Multifunctional noodle modality machine, Guangdong Henglian Food Machine Co., Ltd., China.  Bisma, Lamuru and Arjuna have 27,14-27,68% of amylose content.  The best quality of corn noodle was processed from 100 mesh of corn flour.  The result showed that the best processing condition was obtained at moisture of 70%  and adding 2% of sodium chloride.  Under this condition, corn noodles (Bisma, Lamuru and Arjuna varieties) has elongation between 80,32 – 95,43%, and cooking loss between 5,06 – 5,66%.Key words : corn noodle, forming extruder, amylose content